2013
DOI: 10.3324/haematol.2012.074831
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis of the relationship between response and survival among patients with higher-risk myelodysplastic syndromes treated within azacitidine or conventional care regimens in the randomized AZA-001 trial

Abstract: The phase III AZA-001 study established that azacitidine significantly improves overall survival compared with conventional care regimens (hazard ratio 0.58 [95% confidence interval 0.43-0.77], P<0.001). This analysis was conducted to investigate the relationship between treatment response and overall survival. AZA-001 data were analyzed in a multivariate Cox regression analysis with response as a time-varying covariate. Response categories were "Overall Response" (defined as complete remission, partial remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 19 publications
6
69
1
1
Order By: Relevance
“…34 Similarly, in a secondary analysis of the AZA-001 trial, 91% of high-risk MDS patients responded to treatment within 6 azacitidine cycles and the continuation of treatment further improved the response rates. 35 In our survey, approximately 42% of patients (41.4% of high-risk MDS or CMML patients and 44.4% of AML patients) achieved a treatment response, which is consistent with findings of the previous Dutch, French, Italian, and Austrian studies, in which the overall treatment responses were 48%, 43%, 50%, and 45%, respectively (Table 3). 28,29,33,34 In our survey, the overall response was higher than that reported in the Scottish study in patients with MDS or AML (31%).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…34 Similarly, in a secondary analysis of the AZA-001 trial, 91% of high-risk MDS patients responded to treatment within 6 azacitidine cycles and the continuation of treatment further improved the response rates. 35 In our survey, approximately 42% of patients (41.4% of high-risk MDS or CMML patients and 44.4% of AML patients) achieved a treatment response, which is consistent with findings of the previous Dutch, French, Italian, and Austrian studies, in which the overall treatment responses were 48%, 43%, 50%, and 45%, respectively (Table 3). 28,29,33,34 In our survey, the overall response was higher than that reported in the Scottish study in patients with MDS or AML (31%).…”
Section: Discussionsupporting
confidence: 80%
“…20,28,29,34 The longer med- Furthermore, an additional analysis of the AZA-001 study evaluating the relationship between treatment response and OS revealed that OS of patients with treatment response or HI was significantly improved compared to non-responders; the OS was also significantly higher in patients treated with azacitidine than in those treated with conventional care. 35 The main limitation of our survey is the small number of patients included and a relatively short follow-up period (1 year). Our findings describe the safety and efficacy of azacitidine treatment in this group of patients and must be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the study of azacitidine has revealed nuances of treatment with DNMTi therapy not seen with the use of traditional chemotherapy. These include improved OS, which can occur in the absence of a complete remission (CR),7, 8, 22 a need to treat with as many as 6 treatment cycles prior to achieving maximal response, and hematologic toxicities seen during early treatment tend to decrease if patients can remain on treatment 7, 8, 23…”
Section: Introductionmentioning
confidence: 99%
“…Patients who achieved partial remission (PR) and histologic improvement (HI) demonstrated a survival benefit with azacitidine treatment (13). Patients with stable disease had a survival benefit compared with those with progression, but this was seen in those treated with azacitidine or CCR (14). MDS clones can persist in patients who respond to treatment, suggesting that azacitidine can modulate the function of the cytogenetically abnormal clone and act as a biologic response modifier (15).…”
Section: Azanucleosides In the Mdssmentioning
confidence: 99%